KRITERIA LEADERSHIP DALAM AL-QUR’AN: KAJIAN TAFSIR TEMATIK - Imam Atturmudzi; Muhammad Alif (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
This study aims to analyze the criteria of leadership in the perspective of Qur'an through a thematic interpretation approach. The background of this research is based on the importance of leadership in social life as well as the emergence of moral crises, injustice, and abuse of power in modern leadership. This research employs a qualitative method with a library research design. The data were obtained from Qur’anic verses related to leadership and analyzed using the thematic interpretation (maudhu’i) method through the stages of collecting, classifying, interpreting, and analyzing the verses according to the discussed theme. The results of the study indicate that leadership in the Qur’an is a trust and moral responsibility that must be carried out based on Islamic values. The criteria of Qur’anic leadership include trustworthiness, justice, wisdom, strength and reliability, knowledge and competence, prioritizing deliberation, and becoming a role model in goodness. In addition, a leader is also required to be humble, maintain moral integrity, and prioritize the welfare of society in carrying out leadership responsibilities. This study concludes that the concept of leadership in the Qur’an is not merely oriented toward power, but also toward service, social responsibility, and moral development of society. Therefore, the values of Qur’anic leadership are highly relevant in modern life as guidelines for building leadership that is just, humane, and responsible.